If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(-1x + -10) = 7 Reorder the terms: -1(-10 + -1x) = 7 (-10 * -1 + -1x * -1) = 7 (10 + 1x) = 7 Solving 10 + 1x = 7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 1x = 7 + -10 Combine like terms: 10 + -10 = 0 0 + 1x = 7 + -10 1x = 7 + -10 Combine like terms: 7 + -10 = -3 1x = -3 Divide each side by '1'. x = -3 Simplifying x = -3
| 6+6v=-3(-2v-2) | | 4g-5-3g+8= | | 22-(x+8)=5x-4 | | 5/3(9)-(-14) | | 4(h-2)=44 | | 15y-5-14y+2= | | n^2-4=45 | | 10/6•3/5 | | -13v=-11 | | 2f+7g-7+8g= | | 8rs+9rs+st= | | 7y-11-2y+7=0 | | 2*(3*r)=42 | | 2y+.05x=16 | | -r+1=-5 | | 30+25x=36x-3 | | 2x(3xr)=42 | | -68=-81+m | | 36/(-9)= | | x-(1/8)y=-11 | | 67p+25=350+25P | | 30/(-9)= | | 4af^4-4ak^4=0 | | -144+4x=54-7x | | 1/3(x)=2 | | h=1+-2gk | | -(0.79m+0.227)=-(2.09m+0.838) | | 33x-2=32x+2 | | n-1+2n=-4 | | 18x+7=-5FORX | | 1.2/58 | | 1.2/5.8 |